Bisphosphonate-associated peri-implant fractures: a new clinical entity?: A series of 10 patients with 11 fractures. (3rd September 2015) - Lee, Justine Yun Yu; Soh, Tamara; Howe, Tet Sen; Koh, Joyce Suang Bee; Kwek, Ernest Beng Kee; Chua, David Thai Chong
Abstract : Background and purpose — The current definition of atypical femoral fractures (AFFs) associated with bisphosphonate use includes only de novo fractures. However, in recent years reports of bisphosphonate-associated periprosthetic fractures involving stemmed arthroplasty implants have emerged. In a case series of peri-implant fractures in femurs with plate/screw constructs, we aimed to assess similarities with classical AFFs and how their location may have implications for the pathogenesis and management of AFFs. Patients and methods — We retrospectively identified 10 patients with 11 peri-implant fractures. Results — The patients were ambulant women, mean age 80 (70–92) years. Mean duration of bisphosphonate use was 5 (1–10) years. The peri-implant fractures were sustained an average of 4 years (6 months to 9 years) from the time of index surgery. They were all associated with low-energy mechanisms. 8 fractures occurred near the tip of a plate, while 3 traversed the penultimate screwhole of a plate. The peri-implant fractures showed clinical and radiological features of atypicality such as lateral cortical thickening, simple fracture pattern, and lack of comminution. The patients underwent revision surgery, with bone grafting used in all but 1 case. Radiological union was evident after 2–4 months. Interpretation — Atypical peri-implant fractures of the femur associated with bisphosphonate use may be a new entity. Stress lesions and atypical fractures may tend to develop over stress risers along the operated femur. This finding has implications for the pathogenesis and clinical management of AFFs.